2022
DOI: 10.1111/fare.12734
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of relationship quality and conflict in low‐income parents receiving home visitation services

Abstract: The purpose of this study was to examine changes in relationship quality and couple conflict in low-income parents. Background: When welcoming a new child, couples often report increased conflict and a decline in relationship quality. However, some scholars maintain couples can transition to parenthood with few negative effects. Low-income, unmarried, and experienced parents remain understudied. Method: Utilizing data from a broader parent education project, the study employed dyadic latent growth curve analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Moreover, this research on perceived commitment has focused primarily on White couples who are married or cohabiting. Research on structural commitment among primarily White samples has revealed that cohabiting parents declined in functioning relative to married parents (Kamp Dush et al., 2014) and mothers with non‐residential partners began lower in relationship quality and decreased over time relative to married mothers (Renegar et al., 2023), suggesting some potential benefits from greater structural commitment. In the present study, married mothers and cohabiting mothers did not differ in their initial levels of, or changes, in relationship satisfaction over time, but both had significantly higher initial satisfaction levels than mothers who were not cohabiting with their romantic partner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this research on perceived commitment has focused primarily on White couples who are married or cohabiting. Research on structural commitment among primarily White samples has revealed that cohabiting parents declined in functioning relative to married parents (Kamp Dush et al., 2014) and mothers with non‐residential partners began lower in relationship quality and decreased over time relative to married mothers (Renegar et al., 2023), suggesting some potential benefits from greater structural commitment. In the present study, married mothers and cohabiting mothers did not differ in their initial levels of, or changes, in relationship satisfaction over time, but both had significantly higher initial satisfaction levels than mothers who were not cohabiting with their romantic partner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some research has indicated that structural relationship characteristics such as cohabitation and the duration of the relationship at the time of the baby's birth are related to relationship functioning. Previous research has often compared married and unmarried cohabiting parents (e.g., Kamp Dush et al., 2014; O'Reilly Treter et al., 2021), but has rarely included comparisons with parents who are romantically involved but not cohabiting or married (for an exception, see Renegar et al., 2023). This issue may be particularly important to consider among Black mothers given that 70% of Black women giving birth are not married (Osterman et al., 2023) and many unmarried parents in relationships are not living with their partner at the time of their child's birth (e.g., 35% in Carlson et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This may be especially true when they are also facing enduring vulnerabilities (Neff & Karney, 2007) such as economic marginalization (Moore & Henderson, 2018). At the same time, some couples adapt to changes—such as the birth of a child—with relatively few changes in relationship functioning (Kanter & Proulx, 2019; Leonhardt et al, 2021; Renegar et al, 2022). Given that current relationship quality predicts future relationship functioning and relationship stability, especially for couples from LIEM backgrounds (McClain & Brown, 2017), it is important to explore how correlates (e.g., couple conflict and coparenting alliance) and resources (e.g., emotional support, and instrumental support) are associated with relationship quality in these populations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Couples often experience negative changes in the couple relationship during times of transition, such as the transition to parenthood. Specifically, researchers suggest an increase in conflict and decrease in relationship quality are common (Belsky & Pensky, 1988; Kluwer, 2010), although these changes are not experienced by all couples (see Kanter & Proulx, 2019; Leonhardt et al, 2021; Renegar, Stolz, Baumgardner, Riemnitz, & McCaig, 2022).…”
Section: Introductionmentioning
confidence: 99%